Conventional and wet proofed CuO/Al2O3 catalysts for phenol oxidation: Deactivation studies in a trickle bed reactor - Fenoglio, Rosa Juana (2007)
A large variety of catalytic systems have been studied for the catalytic wet air oxidation of phenolic solutions. Most of them show good activity, but serious stability problems. In this contribution, stability studies were performed over CuO/Al2O3 conventional (CNT) and polytetrafluorethylene coated (C3T) catalysts used for the oxidation of 5 g L-1 phenol solutions in a trickle bed reactor (140 °C and 7 atm of oxygen pressure). For the hydrophilic catalyst, phenol conversion decreased with usage due to the formation of Cu2O and copper oxalate phases. For the wet proofed catalyst, the hydrophobic layer prevented the appearence of those phases, and conversion levels remained practically constant with reaction time. After usage, both catalysts were oxidized at 400 °C and tested for reaction: in the case of the C3T catalyst, the phenol conversion was increased over its initial level; for CNT catalyst, the phenol conversion was also increased, but initial levels were not completely restored. The deactivation mechanism of the CNT catalyst is associated with the formation of the Cu2O and copper oxalate phases during reaction. For catalyst C3T, practically no deactivation was observed.